Evaluation of liver hemangiomas using three different b values on diffusion MR - Bozgeyik, Zulkif; Kocakoc, Ercan; Gul, Yeliz; Dagli, A. Ferda (Elsevier Ireland Ltd, 2010)
Purpose: To determine which diffusion-weighted MR technique (i.e., b-100, b-600, b-1000s/mm(2)) is most useful in depicting liver hemangiomas. We also aimed to assess the effect of lesion size on apparent diffusion coefficient (ADC) values. Materials and methods: Diffusion-weighed MR (DWMR) was performed for 61 hemangiomas in 32 patients. DWMR images were obtained before contrast administration using three different b values of 100, 600, and 1000s/mm(2). ADCs were measured for each lesions and compared with normal liver parenchymal ADCs on different b values. Hemangiomas were subdivided according to lesion size (less than 3 cm and 3 cm or greater). Data were analyzed using SPSS software by analysis of variances (ANOVA) and post hoc values were tested using HSD Tukey test. Results: There was no significant relation between lesion size and ADC values on different b values. Lower ADC values were obtained for higher b values in normal liver tissue and hemangiomas. Although there is significant difference between normal liver tissue and hemangiomas; this is more apparent on b-1000 images (p = 0.022 on b-100, p = 0.003 on b-600, and p = 0.000 on b-1000 images). Variance analysis revealed hemangiomas had higher ADC values than normal liver tissue on b-1000 images. Conclusion: Mean values for ADCs of hemangiomas were lower than ADCs of the normal liver except for b-1000 value. Higher b values are useful for the differentiation between normal liver tissue and hemangiomas. Lesion size does not affect ADC measurement on different b values. (C) 2009 Elsevier Ireland Ltd. All rights reserved.
Keywords: Liver; Hemangioma; DWI; Diffusion-weighted MRI; MRI